Hubungan Kepribadian Proaktif Dengan Perilaku Kerja Inovatif Pada Generasi Millenial - Dhien Amalia Putri (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2020)
The millennial generation is the generation that has dominated the labor market in recent years. This generation is being faced with various challenges due to technological developments that are happening. Current technological developments are forcing the players in the goods and service industries to innovate in order to be able to increase the competitiveness of companies. Innovative work behavior can be raised by individuals in several ways, one of which is with a proactive personality. This study aims to measure the relationship between proactive personality with innovative work behavior in the millennial generation. The study was conducted on 315 millennials who are full time employees in goods and services companies in the city of Surabaya. Innovative work behavior is measured using the Innovative Work Behavior Scale, which is proven to be reliable (α = 0.760), while the proactive personality is measured using the Proactive Personality Scale that has proven to be reliable (α = 0.734). The analysis in this study uses Pearson's Product Moment analysis with a significance value of 0,000 (p <0.05) which shows the relationship between proactive personality and innovative work behavior in the millennial generation. These results indicate that the higher the proactive personality an individual has, the higher the innovative work behavior exhibited by the individual. The results of this study also found a significant relationship between sex, years of service and age on innovative work behavior